Measurements of the angular distributions of muons from Υ decays in pp collisions at sqrt[s] = 1.96 TeV. - Aaltonen, T; Álvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Arisawa, T; Artikov, A; Asaadi, J; et al. (2012)
The angular distributions of muons from Υ(1S,2S,3S) → μ+ μ- decays are measured using data from pp collisions at sqrt[s] = 1.96  TeV corresponding to an integrated luminosity of 6.7  fb(-1) and collected with the CDF II detector at the Fermilab Tevatron. This analysis is the first to report the full angular distributions as functions of transverse momentum p(T) for Υ mesons in both the Collins-Soper and s-channel helicity frames. This is also the first measurement of the spin alignment of Υ(3S) mesons. Within the kinematic range of Υ rapidity |y|<0.6 and p(T) up to 40  GeV/c, the angular distributions are found to be nearly isotropic.